<---- Sponsored ads ------ >

Solve, x2 + x = 0


Solution.

Given equation is x2 + x = 0

Comparing it with the standard Form of Quadratic Equation ax2 + bx + c = 0

a = 1, b = 1, c = 0

As we know, discriminant = b2 - 4ac

Discriminant = (1)2 - 4(1)(0)

Discriminant = 1 - (0)

Discriminant = 1

Since discriminant > 0
Both roots are real and unequal.

Using quadratic formula


Roots(x1, x2) = −b ± √   b2 − 4ac 
         2a          


Roots(x1, x2) = −b ± √ D
         2a          


x1 = −b + √D
         2a          


=   −(1) + √1
         2(1)          


=    -1 + 1
         2          


= 0


x2 = −b - √D
         2a          


=   −(1) - √1
         2(1)          


=    -1 - 1
         2          


= -1


Roots: x1 = 0,     x2 = -1


Sum of roots = -b/a

Sum of roots = -(1)/(1)

Sum of roots = -1


Product of roots = c/a

Product of roots = (0)/(1)

Product of roots = 0
<---- Sponsored ads ----- >

© 2020-2030 Amibba Systems Private Limited. All rights reserved.